Coping with violence in the New Testament - De Villiers, Pieter.; Henten, J. W. van. (Studies in Theology and Religion, 2012)
Violence is present in the very heart of religion and its sacred traditions - also of Christianity and the Bible. The problem, however, is not only that violence is ingrained in the mere existence of religions with their sacred traditions. It is equally problematic to realise that the icy grip of violence on the sacred has gone unnoticed and unchallenged for a very long time. The present publication aims to contribute to the recent scholarly debate about the interconnections between violence and monotheistic religions by analysing the role of violence in the New Testament as well as by offering some hermeneutical perspectives on violence as it is articulated in the earliest Christian writings. Contributors include: Andries G. van Aarde, Paul Decock, Pieter G.R. de Villiers, Ernest van Eck, Jan Willem van Henten, Rob van Houwelingen, Kobus Kok, Tobias Nicklas, Jeremy Punt, Jan G. van der Watt, and Wim Weren.